Digital Dilemmas Exploring Social Media Ethics in Organizations - Kvalnes, Øyvind (Springer Nature, 2020)
Social media is at the core of digital transformations in organizations. Facebook, Twitter, LinkedIn, and other social media platforms widen the scope for rapid and effective communication with stakeholders. They also create a range of new and challenging ethical dilemmas. This open access book categorizes the dilemmas organizations across a range of industries can face when they implement social media to communicate with stakeholders. This book provides a systematic framework for analyzing these ethical dilemmas in social media using the Navigation Wheel. This tool leads the decision-maker through a series of considerations such as legal questions, corporate identity, morality, reputation, and ethics. Finally, the author considers implications for leaders and presents potential solutions to these dilemmas. Based on five years of original research with 250 executive students at a European business school, all of whom work with social media communications in their organizations, this book is the first major study to explore the ethical use of social media across industries and is a valuable resource for researchers and practitioners alike.